A Method for Recruiting Participants from Isolated Islands of Small Island Developing States (SIDS) for Survey Research. Issue 1 (February 2016) - Moosa, Sheena; Koopman-Boyden, Peggy
Representing isolated small island communities through social survey research continues to be challenging. We examine a locally developed method to reach and recruit older people (65+ years) for a survey on well-being in the small island developing state of Maldives. The use of messengers to recruit participants is examined in the context of these isolated islands. The approach allowed for the participation of the isolated island communities in the survey yielding a high response rate. We consider the aspects of this approach for further application to survey research in isolated communities.